Prevalence, attitudes, and knowledge of in-vehicle technologies and vehicle adaptations among older drivers. (April 2018) - Eby, David W.; Molnar, Lisa J.; Zakrajsek, Jennifer S.; Ryan, Lindsay H.; Zanier, Nicole; Louis, Renée M. St.; Stanciu, Sergiu C.; LeBlanc, David; Kostyniuk, Lidia P.; Smith, Jacqui; Yung, Raymond; Nyquist, Linda; et al.
Highlights: 57% of older drivers reported having advanced technologies in their vehicle. Technology prevalence was greater for men and those with higher income and education. The majority of older drivers figured out how to use technologies on their own. Technologies were used frequently and generally thought to make people safer drivers. Of the few vehicle adaptations reported, most older drivers did not work with professionals to make or use adaptations. Abstract: The purpose of the present study was to gain a better understanding of the types of in-vehicle technologies being used by older drivers as well as older drivers' use, learning, and perceptions of safety related to these technologies among a large cohort of older drivers at multiple sites in the United States. A secondary purpose was to explore the prevalence of aftermarket vehicle adaptations and how older adults go about making adaptations and how they learn to use them. The study utilized baseline questionnaire data from 2990 participants from the Longitudinal Research on Aging Drivers (LongROAD) study. Fifteen in-vehicle technologies and 12 aftermarket vehicle adaptations were investigated. Overall, 57.2% of participants had at least one advanced technology in their primary vehicle. The number of technologies in a vehicle was significantly related to being male, having a higher income, and having a higher education level. The majority of respondents learned to use these technologies on their own, with "figured-it-out-myself" being reported by 25%–75% of respondents across the technologies. Overall, technologies were always used about 43% of the time, with wide variability among the technologies. Across all technologies, nearly 70% of respondents who had these technologies believed that they made them a safer driver. With regard to vehicle adaptations, less than 9% of respondents had at least one vehicle adaptation present, with the number of adaptations per vehicle ranging from 0 to 4. A large majority did not work with a professional to make or learn about the aftermarket vehicle adaptation.